Effect of Goniosynechialysis During Phacoemulsification on IOP in Patients With Medically Well-controlled Chronic Angle-Closure Glaucoma. Issue 6 (August 2015) - Lee, Chang-Kyu; Rho, Seung Soo; Sung, Gong Je; Kim, Na Rae; Yang, Jong Yun; Lee, Na Eun; Hong, Samin; Kim, Chan Yun
Abstract : Purpose: To evaluate and compare the efficacy and safety of combined phacoemulsification and goniosynechialysis (PEGS) to phacoemulsification alone (PE) in patients with medically well-controlled chronic angle-closure glaucoma (CACG) with cataracts. Materials: Thirty eyes diagnosed with CACG and requiring cataract surgery from January 2008 to October 2010 were prospectively randomized, 15 each to PE and PEGS. Changes in peripheral anterior synechiae (PAS), intraocular pressure (IOP), anterior chamber depth, and number of antiglaucoma drugs from baseline to 2 months after the operation were analyzed, as were the type and number of complications. Results: The PE group showed decreases in PAS (118.67±95.38 degrees) and IOP (2.33±2.38 mm Hg) and a significant reduction in the number of antiglaucoma drugs (0.53±0.83, P <0.05) from before to 2 months after surgery. The PEGS group showed similar decreases in PAS (114.00±90.95 degrees), and IOP (4.53±4.16 mm Hg) and number of antiglaucoma drugs (1.20±1.32) ( P <0.05). However, the amount of decline in both the groups did not show any significantly difference in PAS, reduction of IOP, or number of antiglaucoma drugs ( P >0.05), The increase in anterior chamber depth from baseline to 2 months after surgery was significantly greater in the PEGS group ( P =0.003). Conclusions: The IOP-lowering effects of PEGS do not differ significantly from those of PE in medically well-controlled CACG patients with cataract. These results suggest that additional goniosynechialysis during phacoemulsification is not necessary in such patients.